CHARACTER EDUCATION VALUES IN THE ALQURAN (STUDY OF ANIMAL VERSES: BEES, CROWS, AND LIONS) - Nurhadi Nurhadi; Doni Putra (STAI Hubbulwathan Duri, 2020)
This study aims to reveal the values of character education described in the verses of the Alquran, especially in animal verses (fauna), namely: bees, crows, and lions. The research method uses the Content Analysis method, with the type of library research. The primary data source is the Tafsir Alquran, the fauna verses and the primary source is the support. The results of his research then as for the values of animal character education in the Alquran, namely: 1) bees have the value of character education a) hard work, b) willing and willing to sacrifice, c) discipline, d) obedient and obedient, e ) trustworthy and responsible, f) independent, g) not looking for position, h) respecting the leader, i) beneficial to other creatures, j) maintaining cleanliness. 2) crows, a) intelligence, b) cooperation, c) faith, d) Islamic educational values. 3) Lions, a) courage, b) affection, c) sincerity, d) patience and e) cooperation. While the relevance of character to education are: a) Understanding of character helps formulate educational goals, b) Understanding of character helps formulate the characteristics and content of the curriculum, c) Understanding of character will help formulate the characteristics of professional teachers, d) Understanding of character will help formulate the code school ethics and discipline, e) Understanding of character can help formulate effective methods and approaches in the learning process, f) Understanding of character can create a conducive educational environment.